THEORETICAL AND METHODOLOGICAL BASIS OF ACCOUNTING IN CAR TRANSPORT ENTERPRISES AND THE REQUIREMENTS OF INTERNATIONAL STANDARDS (World Economics and Finance Bulletin, 2026)
In the thesis, the theoretical and methodological foundations of accounting in road transport enterprises are analyzed in depth. In the study, the impact of specific characteristics of the network (movable assets, distance-related costs, mixed activity structure) on the accounting process was systematically assessed, and aspects of the application of international accounting and auditing standards were analyzed.
Keywords: motor transport; accounting; fixed assets